Regulation of carotenoid and flavonoid biosynthetic pathways in Lactuca sativa var capitate L. in protected cultivation - Harbart, Vanessa; Frede, Katja; Fitzner, Maria; Baldermann, Susanne (Frontiers in Plant Science, 2023)
In the face of a growing world population and limited land, there is an urgent demand for higher productivity of food crops, and cultivation systems must be adapted to future needs. Sustainable crop production should aim for not only high yields, but also high nutritional values. In particular, the consumption of bioactive compounds such as carotenoids and flavonoids is associated with a reduced incidence of non-transmissible diseases. Modulating environmental conditions by improving cultivation systems can lead to the adaption of plant metabolisms and the accumulation of bioactive compounds. The present study investigates the regulation of carotenoid and flavonoid metabolisms in lettuce (Lactuca sativa var capitate L.) grown in a protected environment (polytunnels) compared to plants grown without polytunnels. Carotenoid, flavonoid and phytohormone (ABA) contents were determined using HPLC-MS and transcript levels of key metabolic genes were analyzed by RT-qPCR. In this study, we observed inverse contents of flavonoids and carotenoids in lettuce grown without or under polytunnels. Flavonoid contents on a total and individual level were significantly lower, while total carotenoid content was higher in lettuce plants grown under polytunnels compared to without. However, the adaptation was specific to the level of individual carotenoids. For instance, the accumulation of the main carotenoids lutein and neoxanthin was induced while the β-carotene content remained unchanged. In addition, our findings suggest that the flavonoid content of lettuce depends on transcript levels of the key biosynthetic enzyme, which is modulated by UV light. A regulatory influence can be assumed based on the relation between the concentration of the phytohormone ABA and the flavonoid content in lettuce. In contrast, the carotenoid content is not reflected in transcript levels of the key enzyme of either the biosynthetic or the degradation pathway. Nevertheless, the carotenoid metabolic flux determined using norflurazon was higher in lettuce grown under polytunnels, suggesting posttranscriptional regulation of carotenoid accumulation, which should be an integral part of future studies. Therefore, a balance needs to be found between the individual environmental factors, including light and temperature, in order to optimize the carotenoid or flavonoid contents and to obtain nutritionally highly valuable crops in protected cultivation.